Analisis Pengaruh Kualitas Pelayanan Jasa Terhadap Kepuasan Pelanggan Pt. Nyata Grafika Media Surakarta - Ayuningtyas, Gusti Sekar Arum, Dra. Chuzaimah, M.M (2016)
This study aims to identify and analyze how much influence the quality service to the level of satisfaction felt by customers who use the printing services at PT. Nyata Grafika Media Surakarta. Data collection methods used in this study is a questionnaire, interview, and literature study using likert scale and the method of determining the sample used is convenience sampling as many as 100 samples. The analytical method used is multiple linear regression analysis (multiple linear regression), F test, and t test results showed that the quality service consisting of Reliability (X1), Responsiveness (X2), Assurance (X3), Emphaty (X4) and Tangible (X5) are together have a positive influence with the following regression equation: Y = 4.932 + 0,239X1 + 0,207X2 + 0,327X3 - 0,410X4 + 0,194X5 + 1.569. The results showed that the quality services that include Reliability, Responsiveness, Assurance, Empathy, Tangible had a significant effect on customer satisfaction. Based on the partial test (t test) showed five independent variables found to significantly affect the dependent variable customer satisfaction. Based on F test found that the variable Reliability, Responsiveness, Assurance, Empathy, Tangible significantly together influential in customer satisfaction. Score Adjusted R Square is 0.560 indicates that 56 percent of the variation of customer satisfaction can be explained by the five independent variables used in the regression equation, while 44 percent is explained by other variables outside the five independent variables that used in this studyKeywords: Customer satisfaction, Quality service, Reliability, Assurance, Empathy, Responsiveness, Tangible, Multiple Linear Regression Method, F test and t test.